The Struggle for Life and the Modern Italian Novel, 1859-1925 - Sartori, Andrea (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"Andrea Sartori provides an original reinterpretation of key works by De Roberto, Verga, Pirandello, D'Annunzio, and Marinetti (among many others) by unpacking their use of concepts such as 'struggle for life', 'adaptation', and 'degeneration'. Offering a nuanced and stimulating reading of the use of Darwinian and Darwinist theories in nineteenth- and early twentieth-century Italian literature, The Struggle for Life and the Modern Italian Novel rewrites the history of the Belpaese as it ushered in modernity." -Mimmo Cangiano, University of Venice Ca' Foscari This book explores Darwinism in modern Italian literature. In the years between Italy's unification (1861) and the rise of fascism, many writers gave voice to anxieties connected with the ideas of evolution and progress. This study shows how Italian authors borrowed and reworked a scientific vocabulary to write about the contradictions and the contrasting tensions of Italy's cultural and politicaleconomic modernization. It focuses, above all, on novels by Italo Svevo, Federico De Roberto and Luigi Pirandello. The analysis centers on such topics as the struggle against adverse social conditions in a capitalist society; the risk of failing to survive the struggle itself; the adaptive issues of individuals uprooted from their family and work environments; and the concerns about the heritability of maladaptive characteristics. The book also argues that the hybridization and variation of both narrative forms and collective mindsets describes the modernist awareness of the cultural complexity experienced in Italy and Europe at this time. Andrea Sartori teaches Italian and European Culture at Politecnico of Milan, Italy, for the year 2022-23. He is the author of Scompenso (2010) and L'inventalavoro (2012). He co-edited Perspectives on Italian Difference: Italian Differences in Perspective (2018) and Terry Pinkard's La Fenomenologia di Hegel in Italian (2013).
1 Introduction -- 2 Darwin's Traces -- 3 Svevo: Life and Writing -- 4 De Roberto: Power and Transformism -- 5 Pirandello: Name and Performance -- 6 Conclusion.
Keywords: European literature; Literature, Modern-20th century; Literature, Modern-19th century; Comparative literature; European Literature; Twentieth-Century Literature; Nineteenth-Century Literature; Comparative Literature